Hemocitical responses to environmental stress in invertebrates: a review - Perez, Danielli Giuliano [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer, 2011)
Although invertebrates are recognized by the great facility to accumulate pollutants present in their environment and many of them are used as sentinel species in biomonitoring studies, little is known about the impact of toxicants on the immune system of these animals. In this regard, hemocytes play a fundamental role: these cells circulate freely through the hemolymph of invertebrates and act on the recognition of foreign material to the organism, mediating and effecting the cellular defense, such as phagocytosis, nodulation, and encapsulation. Different morphological types can be recognized but still there is controversy among the researchers about the exact classification of the hemocytes due to the diversity of techniques for the preservation and observation of these cells. In the present study, a review on the main hemocyte responses to environmental stress in different invertebrate organisms is presented, emphasizing the contamination by heavy metals. It is discussed parameters such as: alteration in the number of cells involved in the defense reaction, phagocytic activity, lysosomal responses, and production of reactive oxygen species.
Keywords: Hemocytes; Immunity of invertebrates; Cellular defense; Environmental stress; Heavy metals